2022
DOI: 10.9734/ajmah/2022/v20i1130523
|View full text |Cite
|
Sign up to set email alerts
|

Exam Anxiety among Medical Students in Dhaka City and Its Associated Factors-A Cross-sectional Study

Abstract: Exam anxiety can be term as a mental disorder found in most students. It is a kind of fear and scaredness for which students choose to avoid the feared situations such as exams. A little bit of anxiety is common before and during the examination. Still, it can negatively impact their mental health and academic performances when it is more than the threshold level. The reasons might be expectations and pressure from parents and for competition with other peers. A cross-sectional study was conducted among medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The majority of the studies reviewed con rm that test anxiety negatively affects academic performance (13)(14)(15). Several research have found a signi cant correlation between test anxiety and academic achievement, indicating that higher levels of test anxiety are associated with lower exam scores and lower academic performance (22,23). For example, Green et al (2016) RCT study found that test anxiety has a moderately signi cant negative correlation with USMLE score.…”
Section: Test Anxiety and Academic Achievementmentioning
confidence: 99%
“…The majority of the studies reviewed con rm that test anxiety negatively affects academic performance (13)(14)(15). Several research have found a signi cant correlation between test anxiety and academic achievement, indicating that higher levels of test anxiety are associated with lower exam scores and lower academic performance (22,23). For example, Green et al (2016) RCT study found that test anxiety has a moderately signi cant negative correlation with USMLE score.…”
Section: Test Anxiety and Academic Achievementmentioning
confidence: 99%